(untitled) (Research, Society and Development, 2024)
Oral-sinus communication (OSC) is a direct communication between the maxillary sinus and the oral cavity. It often occurs in maxillary premolar and molar extractions due to the proximity of the maxillary sinus floor to the apex of these dental elements. Being a common surgical complication in the dental environment, there must be an understanding of the possible clinical and therapeutic management to be chosen for each situation. Therefore, this work aims to address the clinical and surgical management of oral-sinus communication, highlighting the advantages and disadvantages of each technique, in order to guide the dental surgeon on the importance of good planning and choosing the most appropriate treatment for each specific case. This study consists of a narrative literature review to address the clinical and surgical management of oral-sinus communication. The search was carried out in November 2023, in the PubMed databases, and to compose this review, 20 articles were selected that discussed clinical and surgical management for the treatment of oral-sinus communication published between 2013 and 2023 in the English language. It is observed that OSC repair can occur both clinically through the formation of a blood clot, in cases of communication less than 3 mm, and surgically, in larger defects, for which the literature points to several surgical treatment options, the choice of which depends on the skill of the professional, patient needs, location of the communication, height of the alveolar ridge and absence of infection.